PENGARUH ICE BREAKING TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SDN 182 PEKANBARU - Sabaria Romaito; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effect of ice breaking on the motivation to learn Indonesian for class V students at SDN 182 Pekanbaru. Ice Breaking is a straightforward, light and compact game or action that can change the atmosphere of being frozen, tense, tired or lethargic in educational and learning activities. Because this is one of the factors that can influence student learning motivation. The type of research used in this research is one group pretest-posttest design with the number of samples in this research being class V C students, totaling 32 students. The data collection technique uses a questionnaire with 18 questions. The results obtained in this research were pretest with an average of 4.7188 and posttest with an average of 7.5625. pretest and posttst experienced an increase of 2,843. The research results also show that the significance obtained is 0.000 < 0.05, so that Ha is accepted and Ho is rejected, this shows that there is an influence of ice breaking on the motivation to learn Indonesian for class V students at SDN 182 Pekanbaru.